AMP 348 - Retailing - February - March 2001 - PPP, Pusat Pengajian Pengurusan (2001)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2000/2001 February/March 2001 AMP 348 - Retailing Time : 3 hours